Education Financing and Assessment in Improving the Quality of Education In Indonesia - Helma Rusina (CV. ADIBA AISHA AMIRA, 2022)
The education process cannot run without costs, the cost of education is all expenditures, whether in the form of money or not, as an expression of the responsibility of all parties to the development of education. Through education, a quality and superior generation is born, so education is an important factor to make it happen. Education funding is needed for school programs, teacher salaries, employee salaries and other needs that can support the achievement of the vision and mission. Then the assessment of the learning program also needs to be carried out properly, with the aim of knowing the extent to which the learning program affects the improvement of the quality of education